Health promoting behaviors in adolescence: validation of the Portuguese version of the Adolescent Lifestyle Profile - Sousa,Pedro (2015)
OBJECTIVE: Reliable and valid instruments are essential for understanding health-promoting behaviors in adolescents. This study analyzed the psychometric properties of the Portuguese version of the Adolescent Lifestyle Profile (ALP).METHODS: A linguistic and cultural translation of the ALP was conducted with 236 adolescents from two different settings: a community (n = 141) and a clinical setting (n = 95). Internal consistency reliability and confirmatory factor analysis were performed.RESULTS: Results showed an adequate fit to data, yielding a 36-item, seven-factor structure (CMIN/DF = 1.667, CFI = 0.807, GFI = 0.822, RMR = 0.051, RMSEA = 0.053, PNFI = 0.575, PCFI = 0.731). The ALP presented a high internal consistency (a = 0.866), with the subscales presenting moderate reliability values (from 0.492 to 0.747). The highest values were in Interpersonal Relations (3.059 ± 0.523) and Positive Life Perspective (2.985 ± 0.588). Some gender differences were found. Findings showed that adolescents from the clinic reported an overall healthier lifestyle than those from the community setting (2.598 ± 0.379 vs. 2.504 ± 0.346; t = 1.976, p = 0.049).CONCLUSION: The ALP Portuguese version is a psychometrically reliable, valid, and useful measurement instrument for assessing health-promoting lifestyles in adolescence. The ALP is cross-culturally validated and can decisively contribute to a better understanding of adolescent health promotion needs. Additional research is needed to evaluate the instrument's predictive validity, as well as its clinical relevance for practice and research.